Influence of Effective Planning of Work Process on Competitive Advantage of Numerical Derivative Industries. A Critical Literature Review - Kariuki, Robert Kariuki (International Journal of Modern Statistics, 2022)
Purpose: Adaptive capability is defined as a firm's ability to identify and capitalize on emerging market opportunities. The overall objective of this study was to examine influence of effective planning of work process on competitive advantage of numerical derivative industries. A critical literature review Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. Findings: The study also concluded that organizational transformation affects competitive advantage in the numerical machining industries positively. The study showed that new performance measures enhance sustained profitability and revised compensation and training strengthens customer loyalty. The study further revealed that continuous improvement determines brand recognition. Unique Contribution to Theory, Policy and Practice: The study recommends that management in firms should engage with emerging markets more closely. This can be done through planning and determining the cost advantages as well as the operational costs in order to keep itself competitive. The study recommends that international business participant should have an understanding of economics, finance, marketing and strategy, a social understanding of culture and managing across culture. The Numerical Machining industries should plan and launch next generation line extensions with precision and advice from physicians and patients. The study recommends that the patent protection should have lapsed and the corporation set up a defined strategy.